2012
DOI: 10.1139/z2012-019
|View full text |Cite
|
Sign up to set email alerts
|

Critical swim speed and fast-start response in the African cichlidPseudocrenilabrus multicolor victoriae: convergent performance in divergent oxygen regimes

Abstract: Dissolved oxygen (DO) can be a strong predictor of intraspecific variation in morphology and physiology in fishes. In the African cichlid Pseudocrenilabrus multicolor victoriae Seegers, 1990, fish reared under low DO develop larger gills, deeper bodies, and larger, wider heads than full siblings reared under high DO, which could influence swim performance. In this study, we compared critical swim speed (Ucrit) and fast-start swimming in F1-generation fish from two field populations (one high and one low DO) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…In this case, it is possible that bridle shiner are sensitive to turbidity but can compensate physiologically such that, when exposed to clear water after a prolonged exposure to turbid water, they display higher than expected swimming speeds. Such an effect has been shown in a cichlid fish, Pseudocrenilabrus multicolor , acclimated to low and high dissolved oxygen (DO): fish reared in a low DO environment and tested in high DO showed elevated critical swimming speed compared with those fish acclimated to high DO and tested in the same environment (Gotanda et al ., ). To test this compensatory hypothesis for bridle shiner and the other four shiner species, reciprocal experiments need to be performed in which fish acclimated to clear and turbid water are tested in both.…”
Section: Discussionmentioning
confidence: 97%
“…In this case, it is possible that bridle shiner are sensitive to turbidity but can compensate physiologically such that, when exposed to clear water after a prolonged exposure to turbid water, they display higher than expected swimming speeds. Such an effect has been shown in a cichlid fish, Pseudocrenilabrus multicolor , acclimated to low and high dissolved oxygen (DO): fish reared in a low DO environment and tested in high DO showed elevated critical swimming speed compared with those fish acclimated to high DO and tested in the same environment (Gotanda et al ., ). To test this compensatory hypothesis for bridle shiner and the other four shiner species, reciprocal experiments need to be performed in which fish acclimated to clear and turbid water are tested in both.…”
Section: Discussionmentioning
confidence: 97%
“…The burst speed a fish uses is used for a short duration in time in order to navigate rapid increases in flow, as seen through a V slot, while the prolonged swimming speed as tested within this study gives an indication of speeds achievable within resting pools. Pseudocrenilabrus philander in this study had a U crit comparable Gotanda et al (2012). The other fish species, which were larger in size, had higher swimming durations giving higher T i values (lowest T i 67 min and the highest T i 150 min); an individual fish therefore swam for 2 h 30 min.…”
Section: Discussionmentioning
confidence: 48%
“…These include breeding reaches, which aid in genetic dispersal, as well as foraging, avoiding predators and moving away from unfavourable environmental conditions (Ross, 2015). In order to support successful migration and diversity of fish species within a system, fishways need to be designed to cater for the weakest-swimming species (Garcia de Leaniz, 2008;Pon, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, larger head size in hypoxia-reared fish may not have a significant effect on swim performance. In a study of P. multicolor, Gotanda et al (2012) found no difference in the burst speed or critical swim speed of fish reared under low-DO and high-DO when tested in their home environment, suggesting that divergent phenotypes are capable of achieving the same performance.…”
Section: Figurementioning
confidence: 99%